FATORES CRÍTICOS DE SUCESSO NO LANÇAMENTO (START-UP) DE PNEUS REMOLDADOS DE AUTOMÓVEIS, CAMIONETAS, CAMIONETES E SEUS REBOCADOS LEVES CERTIFICADOS PELOS ORGANISMOS ACREDITADOS PELO INMETRO - Carneiro, Oscar Augusto Cunha (2006)
This research is intended to validate the critical success factors for remould tires products start-up. Those critical success factors have been identified through Porter s prognostics for new product launching. The theoretical referential used in this research were Rockart s critical success factors, Porter s life cycle model. Having the existing literature about the subject and prognostic deductions as start points for this study, five critical success factors have been identified and validated through research and a questionnaire applied in remould tires factories plants and remould tires suppliers in the State of Rio de Janeiro, Brazil.